2009
DOI: 10.1128/jcm.01181-08
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Human Immunodeficiency Virus Type 1 Infection in Infants by Use of Dried Blood Spots and an Ultrasensitive p24 Antigen Assay

Abstract: We tested 617 dried blood spots (DBS) from human immunodeficiency virus-exposed infants from five countries using an ultrasensitive p24 antigen assay (Up24). The sensitivity was 94.4% (67/71) and the specificity was 100% (431/431) for infants with DBS specimens <20 months old; DBS older than 30 months demonstrated only 72.2% sensitivity (39/54) (P < 0.001) but displayed 100% specificity (61/61).Several factors reduce diagnosis of human immunodeficiency virus (HIV) in infancy in resource-limited settings. Simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…These findings are promising because dried blood spot analysis is common for infant diagnosis in rural areas. 37 Compared with standard or reverse transcription PCR, p24 immunoassays are cheaper (up to US$ 10 in Africa) and less demanding of resources, which makes them a worthwhile option in clinics with limited access to more expensive tests. 11 However, p24 immunoassays are not widely used owing to a lack of validation data.…”
Section: Early Infant Diagnosismentioning
confidence: 99%
“…These findings are promising because dried blood spot analysis is common for infant diagnosis in rural areas. 37 Compared with standard or reverse transcription PCR, p24 immunoassays are cheaper (up to US$ 10 in Africa) and less demanding of resources, which makes them a worthwhile option in clinics with limited access to more expensive tests. 11 However, p24 immunoassays are not widely used owing to a lack of validation data.…”
Section: Early Infant Diagnosismentioning
confidence: 99%
“…Furthermore, Gottlieb (Gottlieb et al, 2002) and Kostrikis (Kostrikis et al, 2002) have shown that HIV DNA levels independently predict disease progression. Together, these data suggest that HIV-1 DNA (and/or HIV-1 RNA) measurements from DBS, already shown to be useful for diagnosis and drug resistance testing (Buckton et al, 2008; Cachafeiro et al, 2009; Ikomey et al, 2009; Kerr et al, 2009), should be further explored as a marker of disease progression- risk in situations where plasma VL assays are impractical because of cost and resource limitations.…”
Section: Discussionmentioning
confidence: 90%
“…Since age of testing and duration of storage of DBS may also affect the performance characteristics of Up24 antigen detection in DBS9,13, we examined, using a logistic regression model with 8-fold NCSD as the cut-point, their effect on the sensitivity and specificity of Up24 antigen assay. No significant difference in the median age (p = 0.87) or duration of storage (p=0.246) between the samples with negative and positive PCR results were found.…”
Section: Resultsmentioning
confidence: 99%
“…Frequent HIV-testing of infants with ongoing exposure to HIV through breast-feeding is also deterred. Evaluation of ultrasensitive p24 (Up24) antigen assays on liquid or dried plasma28 or blood spots913, that is more feasible for RCS, yielded sensitivities of 84–98% and specificities of 98–100%. More recently, Mwapasa et.…”
Section: Introductionmentioning
confidence: 99%